The Effect of Work Stress, Motivation, and Work Environment on Employee Performance with Work-Life Balance as A Moderating Variable on Employees - Arifin Sugianto; Masdar Mas’ud; Abbas Selong (Manunggal Halim Jaya, 2025)
This study aims to investigate the impact of work stress, motivation, and work environment on employee performance, with work-life balance serving as a moderating variable, among PLN UP3 Baubau employees. The data for this study were obtained from employees of PLN UP3 Baubau in 2025, who were willing to participate as respondents. This research utilizes primary data collected through direct field research, where questionnaires/statements were distributed to respondents. The sample was collected using the census method, as the sample size is small, representing the entire population of 92 employees. Data analysis was conducted using descriptive statistical analysis and Partial Least Squares (PLS). The results of this study reveal that work stress, motivation, and work environment have a positive and significant impact on employee performance at PLN UP3 Baubau. Work stress, at a manageable level, can motivate employees to become more focused and productive; however, excessive stress can have adverse effects. Strong motivation increases employees' enthusiasm and commitment to achieving the company's goals, while a comfortable and supportive work environment improves focus and productivity. Furthermore, work-life balance enhances the relationship between work stress, motivation, and the work environment, positively impacting performance. Employees who maintain a good balance between work and personal life tend to be more motivated and efficient in their work. Therefore, PLN UP3 Baubau management needs to improve these aspects to support optimal employee performance on a continuous basis.